Who Is a Creative Person? Conceptualisation of creativity by people with autism spectrum disorder. - Gut, Arkadiusz; Moszyńska, Małgorzata; Reszuta, Natalia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Arkadiusz Gut, Małgorzata Moszyńska, Natalia Reszuta, Who Is a Creative Person? Conceptualisation of creativity by people with autism spectrum disorder. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 373–387. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.17 A growing body of literature has focused on individuals with autism spectrum disorder who are entering adulthood. Thus, one of the main topics is social interactions and the issue of their functioning in professional contexts. Researchers focus their attention on those individuals’ folk theories that are also crucial in the lives of the normative sample. One of the key folk theories that guide our professional lives is a folk image of the creative person. The folk theory is nothing more than tacit knowledge held by a group of people. It is a system of beliefs and an inner standard of assessment that serves us to explain, for example, why we believe that someone is creative or when we assess the effects of their work. The aim of this paper is to present chosen findings from our study of the folk theory of creativity and creative person using a sample of persons with an autism spectrum disorder. We used a reversed version of Klaus Urban’s and Hans Jellen’s Test for Creative Thinking – Drawing Production (TCT-DP) where respondents selected previously prepared drawings, instead of making them. Their task was to select the most and least creative drawings and rank all the drawings according to their level of creativity. We also measured respondents’ levels of creative efficiency and creative identity.